2017
DOI: 10.7717/peerj.3831
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sustained attention and aerobic fitness in a group of young adults

Abstract: BackgroundA growing set of studies has shown a positive relationship between aerobic fitness and a broad array of cognitive functions. However, few studies have focused on sustained attention, which has been considered a fundamental cognitive process that underlies most everyday activities. The purpose of this study was to investigate the role of aerobic fitness as a key factor in sustained attention capacities in young adults.MethodsForty-four young adults (18–23 years) were divided into two groups as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
(70 reference statements)
3
20
1
Order By: Relevance
“…For example, promoting the implementation of trained coaches could be a possible approach to integrate holistic and health-promoting training concepts into the daily routines of eSports players. Although research identifying the essential skills for success in eSports is limited, it may be assumed that fitness training and training content from traditional sports may also benefit skills that are necessary for good eSports performance like, e.g., sustained attention [45] or reaction time [46,47]. Right now, about half of the respondents, and predominantly those who compete in official tournaments and leagues, complete structured training but most of it takes place without a coach and almost solely in the digital environment.…”
Section: Key Resultsmentioning
confidence: 99%
“…For example, promoting the implementation of trained coaches could be a possible approach to integrate holistic and health-promoting training concepts into the daily routines of eSports players. Although research identifying the essential skills for success in eSports is limited, it may be assumed that fitness training and training content from traditional sports may also benefit skills that are necessary for good eSports performance like, e.g., sustained attention [45] or reaction time [46,47]. Right now, about half of the respondents, and predominantly those who compete in official tournaments and leagues, complete structured training but most of it takes place without a coach and almost solely in the digital environment.…”
Section: Key Resultsmentioning
confidence: 99%
“…In assessing sustained attention ability, there are many types and versions of sustained attention tests. The most frequent test used was the Psychomotor Vigilance Test (PVT) [13][14][15][16][17][18], followed by the Continuous Performance Test and its many versions such as Identical Pairs [19], and Conners'-II [20]. Other sustained attention tests are Digit Vigilance Test [21]; Picture Deletion Task Performance [22]; Rapid Visual Processing [23]; and Visual Pursuit Test [24].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced physical or cardiovascular fitness is one of the main consequences of the regular practice of physical exercise that has been related to cognitive performance 4,10-12 . In the particular case of vigilance, our studies showed that higher-fit individuals outperformed lower-fit individuals in the PVT 8,13,14 . The evidence comes from both behavioural (RT) and electrophysiological measures (event related brain and cardiac potentials).…”
Section: Introductionmentioning
confidence: 65%
“…However, those RT group differences from the single studies might still be meaningful but explained by the influence of an unknown (uncontrolled) variable. Moreover, in the studies showing positive results, group differences were not only seen in terms of RT but also in accuracy performance in an oddball task (with much lower RT demands than the PVT; see Ciria et al 13 ), and, more importantly, in task-related cardiac and electroencephalographic measures 8,14,39 . If those group differences were to be true, the result of the present analysis suggests that they were not due to mere differences in cardiovascular fitness.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation